MYB30 Is a Key Negative Regulator of Arabidopsis Photomorphogenic Development That Promotes PIF4 and PIF5 Protein Accumulation in the Light. Issue 7 (5th May 2020) - Yan, Yan; Li, Cong; Dong, Xiaojing; Li, Hong; Zhang, Dun; Zhou, Yangyang; Jiang, Bochen; Peng, Jing; Qin, Xinyan; Cheng, Jinkui; Wang, Xiaoji; Song, Pengyu; et al.
Abstract : The MYB transcription factor MYB30 negatively regulates photomorphogenesis and promotes PIF4 and PIF5 protein accumulation under prolonged red light irradiation. Abstract: Phytochromes are red (R) and far-red (FR) light photoreceptors in plants, and PHYTOCHROME-INTERACTING FACTORS (PIFs) are a group of basic helix-loop-helix family transcription factors that play central roles in repressing photomorphogenesis. Here, we report that MYB30, an R2R3-MYB family transcription factor, acts as a negative regulator of photomorphogenesis in Arabidopsis ( Arabidopsis thaliana ). We show that MYB30 preferentially interacts with the Pfr (active) forms of the phytochrome A (phyA) and phytochrome B (phyB) holoproteins and that MYB30 levels are induced by phyA and phyB in the light. It was previously shown that phytochromes induce rapid phosphorylation and degradation of PIFs upon R light exposure. Our current data indicate that MYB30 promotes PIF4 and PIF5 protein reaccumulation under prolonged R light irradiation by directly binding to their promoters to induce their expression and by inhibiting the interaction of PIF4 and PIF5 with the Pfr form of phyB. In addition, our data indicate that MYB30 interacts with PIFs and that they act additively to repress photomorphogenesis. In summary, our study demonstrates that MYB30 negatively regulates Arabidopsis photomorphogenic development by acting to promote PIF4 and PIF5 protein accumulation under prolonged R light irradiation, thus providing new insights into the complicated but delicate control of PIFs in the responses of plants to their dynamic light environment.